Descomposition of crop residues under no-till management : Wheat, corn, soybeans and wheat after corn or soybeans - Ernst, O.; Bentancur, O.; Borges, R. (Agrociencia Uruguay, 2002)
The rate of decomposition of corn, wheat and soybean residues located on the soil surface and its modification through the crop sequence (soybean-wheat and corn-wheat) was studied. Dry weight and N concentration during 248 days was determined. The rate of decomposition of the soybean stubble was significantly higher than corn and wheat stubble (p<0,05). As a result of an increase in the amount of N immobilized the N concentration increased with time in corn and wheat. In soybean the N concentration and the dry weight were proportionally reduced and the amount of immobilized N in the stubble descended throughout the period. The wheat straw decomposition on soybean stubble was faster than on corn stubble. Difference in the amount of immobilized N did not exist on soybean or maize stubble but the time of N immobilization was significantly lower on soybean residue (p<0,05).